2018
DOI: 10.1039/c8py01207e
|View full text |Cite
|
Sign up to set email alerts
|

Influence of amide-containing side chains on the mechanical properties of diketopyrrolopyrrole-based polymers

Abstract: An efficient strategy to modify the mechanical properties of conjugated polymers has been developed through the incorporation of amide moieties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 42 publications
4
79
0
Order By: Relevance
“…Notably, P187 , with high contents of amide groups in the side chains still maintain good solubility in organic solvents. They also demonstrated that the introduction of imide groups in the side chains could effectively enhance the mechanical properties of polymers P184–P186 to afford stretchability and morphology healing …”
Section: Side Chains With Heteroatoms and Functional Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, P187 , with high contents of amide groups in the side chains still maintain good solubility in organic solvents. They also demonstrated that the introduction of imide groups in the side chains could effectively enhance the mechanical properties of polymers P184–P186 to afford stretchability and morphology healing …”
Section: Side Chains With Heteroatoms and Functional Groupsmentioning
confidence: 99%
“…Hydrogen bonding (H bonding) has been widely used to tune intermolecular interactions and self‐assembly structures by considering its relative bonding strength and directionality . On the basis of this consideration, as shown in Scheme and Figure , some of us incorporated urea groups in the side chains of DPP‐based polymers P175–P177 .…”
Section: Side Chains With Heteroatoms and Functional Groupsmentioning
confidence: 99%
“…Those potential weak interactions include: π–π interactions, hydrogen bonds, and metal‐ligand coordination bonds. Many weak interaction bonds were successfully designed into conjugated polymers to endow a self‐healing ability into conjugated polymers. Previous works by the Bao group are great examples for demonstrating this capability.…”
Section: Future Lookmentioning
confidence: 99%
“…Nuclear magnetic resonance (NMR) and variable temperature Fourier transform infrared (FT-IR) spectroscopy were taken to ascertain the formation of interchain hydrogen bonds. Compared to the investigation of DPP-based polymers from Simon et al [ 30 ], we further studied the influence of amide-containing proportion on solution gelation, which is also significant for the solution-processed technologies in optoelectronics. Most importantly, we developed a practical method for measuring the intrinsic mechanical properties of thin films taking advantage of the conventional tensile strain instrument (dynamic mechanical analyzer, DMA), which is assisted by a hollow substrate (PMMA).…”
Section: Introductionmentioning
confidence: 99%